Post a New Question

substitution method

posted by .

Solve by substitution method please help me solve this. I do not know how to do this at all. The question is
3x+8y=33 and x=31-6y I know that I have to plug x into the first x like 3(31-6y)+ 8y = 33 but i do not know what to do from there.

  • substitution method -

    Okay so on the first side you have 3 which needs to be distributed to both the 31 and the -6y. On the left side you will end up with 93-18y+8y=33. Now you have to finish solving for y. Add 8y to -18y then subtract 93 from both sides. I think you can take it from here. Let me know if you need more help.

  • substitution method -

    I do need more help...

  • substitution method -

    (1)3x + 8y = 33
    (2) x = 31 - 6y
    when using substitution method, first you choose an equation (either of the two given) and express one of the variables in term of the other,, in this case we choose the equation (2) since x is already expressed in terms of y:
    x = 31 - 6y
    then substitute this to equation (1):
    3(31 - 6y) + 8y = 33
    93 - 18y + 8y = 33
    -10y = -60
    y = 6
    now, substituting this value of 'y' to either equations (in this case, into equation (2)) to get x:
    x = 31 - 6y
    x = 31 - 6(6)
    x = 31 - 36
    x = -5

    so there,, :)

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question